Civic Education in Estonia: Democratic or Authoritarian - Haav, Karel (JSSE - Journal of Social Science Education, 2008)
The paper distinguishes between traditional formal and social theoretical concepts in education for democracy. On this basis, both Estonian and EU civic education systems are critically analysed. In both cases, the political literacy is not covered with adequate social theoretical concepts. Traditionally, there is a formal description of main political institutions outside of real social relations. Many social scholars have revealed that such an education but contributes to reproduction of the existing social structures. The Author develops a social theoretical approach to democracy and civic education. It relies on main social dichotomies like that of social actors and social structures, and institutional organization theory. It defines main social actors and models of decision making in main social spheres (economy, politics and education). These concepts are linked to social values (individual freedom and prosperity or social equality, solidarity and well-being) and social outcomes (effectiveness and justice). The author also uses these concepts to describe and analyze his students’ democratic knowledge, attitudes and experiences. An integration of social theoretical concepts and practices enables to achieve the ideal goals of democracy education. The paper also critically evaluates the existing civic education system (syllabus, textbooks and national examinations) in Estonia. The system focuses on delivery of some arbitrary texts. In schools with Russian instruction, the authoritarian Estonian civic education strengthens the authoritarian national attitudes of Russian students. As a result, it counteracts to the national integration of Russian students with the Estonian state.